Beyond the Survivor island representations of American and Filipino cultures of competition in Survivor : Micronesia and Survivor : Philippines - De Jesus, Dale Ramallosa 1990- (2012)
"The Survivor series has been on the air for more than a decade now and with that amount of time, a number of versions have spawned from it and the Philippines was no stranger. In 2008, when Survivor: Micronesia was being shown in America, Survivor: Philippines was making its first wave as well. Both Survivor versions seemed to represent the American and Filipino culture that it guaranteed to represent, but how truthful are these representations? Beyond the Survivor Island explores the American and Filipino cultural constructs portrayed in Survivor: Micronesia and Survivor: Philippines through a textual analysis of the show's visual and aural patterns. The cultures of competition in the show will be the focal point of the study since it is this theme that moves the Survivor series forward. Besides the differences of both versions, this study deems it more important to explore the similarities in the representation of the American and Filipino cultures of competition. This study argues that the culture industry machinery and its imperative to demand profit, circulate a disparate propaganda, standardize competition, and deceive the audience are the reasons why the Survivor versions are made to appear culturally different when they are fundamentally the same."